TAKWIL DAN TAFSIR - Candra Yani, Lili Epi; Aulia, Rara; Hasibuan, Adery Septian (JIMR : Journal Of International Multidisciplinary Research, 2024)
Takwil and tafsir are two methods of interpreting the Koran which have different approaches to understanding the Islamic holy text. Tafsir focuses on explaining the literal and explicit meaning of the verses of the Qur'an by relying on the context of language, history and tradition. This method aims to provide a clear and direct understanding of the message of the Qur'an based on an appropriate interpretation of the words used in the text. Meanwhile, takwil is more interpretive and tends to look for the inner or symbolic meaning contained behind the visible words. Takwil is used to understand verses that have ambiguous or metaphorical meaning, with the aim of uncovering a deeper spiritual or philosophical essence. Although they differ in approach, tawwil and tafsir complement each other in an effort to provide a comprehensive understanding of the Qur'an, as well as playing an important role in the intellectual and spiritual traditions of Islam.